Development of a new Lindqvist-like Fe6 cluster secondary building unit for MOFs. Issue 72 (20th August 2019) - Lin, Li-Dan; Li, Zhong; Zhao, Dan; Liu, Jin-Hua; Li, Xin-Xiong; Zheng, Shou-Tian
Abstract : In this work, a novel Lindqvist-likeFe6 cluster was introduced as an SBU to construct a new family of Fe-cluster organic frameworks. Abstract : This work demonstrates a new Lindqvist-like [FeIII6(μ6 -O)L4 Cl6 ] 2− (Fe6, L = 2-(hydroxymethyl)-2-(pyridin-4-yl)-1, 3-propanediol) cluster for the construction of a novel class of Fe-cluster organic frameworks. The novelFe6 cluster can be used to build not only a homometallic MOF, but also a heterometallic MOF by introducing copper halide clusters to the reaction system. In particular, the heterometallic MOF achieved a skillful combination ofFe6 SBU and cuprous–halide clusters for the first time. Our synthesis strategy opens up an effective avenue to novel Fe-cluster-based MOF materials.